ANALISIS PROSES BISNIS DAN LAYANAN PENERBIT BUKU ONLINE ANDAMARI CREATIVE - Rizqiyatul Khoiriyah; Dewi Afriati (Jurnal Ilmiah Sistem Informasi, 2022)
Information technology (IT) plays an important role in the development and sustainability of the business and transforms the business that is run. With the support of information technology in the course of an organization's business processes, it is hoped that business goals can be realized properly and appropriately. This series of activities or business processes are monitored and evaluated regularly so that the stages can change to suit the needs of the organization. Andamari Creative is an indie book publisher that is ready to help writers to publish their books. In its development, Andamari has carried out business processes and provided services to writers and other users. For business processes to continue running well, analysis and evaluation are needed to find deficiencies and identify opportunities for improvement. Therefore, this study aims to analyze the business processes and information technology (IT) services provided by the online book publisher Andamari Creative. Data collection techniques by conducting interviews and observations. Furthermore, the analysis is carried out descriptively by analyzing the course of business processes, services, and deficiencies in them. The results of the study indicate that the ongoing business processes and services can be analyzed and some strengths and weaknesses can be found. From these shortcomings, recommendations for improvement are proposed to improve Andamari Creative's business processes and services in the future